Perancangan Sistem Solar Tracker Single-Axis Berbasis ANFIS - Farhan Saumi Abdillah; Sofia Pinardi; Harry Ramza (Prosiding Seminar Nasional Teknoka, 2024)
Static solar panel systems have limitations in optimally capturing energy due to the sun's continuously changing position throughout the day. This study aims to design a single-axis solar tracking system on the altitude axis using the Adaptive Neuro-Fuzzy Inference System (ANFIS) method through MATLAB software. The dataset, consisting of time variables (month, day, hour, and minute) as input and the sun's altitude angle as output, was obtained from the timeanddate.com website. The ANFIS processing focused on minimizing error in the form of Root Mean Square Error (RMSE). The results showed that the ANFIS approach achieved an RMSE of 0.51 for training data and 0.56 for testing data. This system can accurately predict the sun's altitude angle, supporting the development of single-axis solar tracking systems.